2010
DOI: 10.1248/cpb.58.1447
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte Changes the Binding Affinity and Mode of Interaction of Minor Groove Binder Hoechst 33258 with Calf Thymus DNA

Abstract: The bis-benzimidazole molecule Hoechst 33258 ( Fig. 1) is an important DNA minor groove binding ligand.1) Interaction of Hoechst 33258 has been extensively studied using oligonucleotides.2-5) Different aspects of this interaction viz., physicochemical, thermodynamics, NMR, X-ray crystallography, in silico simulation are now well established. 3,[6][7][8][9][10][11] From the classical observation on the ability of Hoechst 33258 binding in the AT rich region of minor groove of DNA. Synthetic chemists have designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…In contrast, high selectivity of anionic ligands to the G-quadruplex over dsDNA has been reported, although the studies on anionic ligands have been only a few due to their lower affinity for G-quadruplexes than cationic ones. , Because of this high selectivity, anionic G-quadruplex ligands inhibit telomerase very efficiently, even in the presence of excess dsDNA. ,, Moreover, molecular crowding (MC), which mimics the high concentration of biomolecules in cells, , critically affects properties and reactions of biomolecules, including dsDNA , and G-quadruplex DNA, by altering properties of the solution, including a decrease in the dielectric constant and water activity, ,, and an increase in viscosity and excluded volume . Systematic studies demonstrated that MC reduces binding between dsDNA and a variety of dsDNA ligands including intercalators and groove binders . Furthermore, Tan’s group recently reported that MC also reduces binding between the telomeric G-quadruplex and cationic G-quadruplex ligands, including TMPyP4, and their inhibition of telomerase .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high selectivity of anionic ligands to the G-quadruplex over dsDNA has been reported, although the studies on anionic ligands have been only a few due to their lower affinity for G-quadruplexes than cationic ones. , Because of this high selectivity, anionic G-quadruplex ligands inhibit telomerase very efficiently, even in the presence of excess dsDNA. ,, Moreover, molecular crowding (MC), which mimics the high concentration of biomolecules in cells, , critically affects properties and reactions of biomolecules, including dsDNA , and G-quadruplex DNA, by altering properties of the solution, including a decrease in the dielectric constant and water activity, ,, and an increase in viscosity and excluded volume . Systematic studies demonstrated that MC reduces binding between dsDNA and a variety of dsDNA ligands including intercalators and groove binders . Furthermore, Tan’s group recently reported that MC also reduces binding between the telomeric G-quadruplex and cationic G-quadruplex ligands, including TMPyP4, and their inhibition of telomerase .…”
Section: Introductionmentioning
confidence: 99%
“…Double-stranded ctDNA exhibits a negative Cotton effect at 245 nm corresponding to backbone helicity and a positive Cotton effect at 275 nm arising from nucleobase π–π stacking in B-conformation. As the peptide concentration increased, the ellipticity at 275 nm gradually decreased along with a concomitant redshift of the signal due to the interaction of peptides with ctDNA (Figure A, B). , The negative Cotton effect at 245 nm also moderately decreased with an increasing peptide concentration, indicating helicity distortion upon peptide binding. These results correlated with displacement assay data obtained by using the minor groove binding Hoechst dye.…”
Section: Resultsmentioning
confidence: 92%
“…[C 50 of ligand] is the concentration of ligand at 50% reduction of Hoechst fluorescence. The calculated value of K Hoechst = 4.75 × 10 7 …”
Section: Methodsmentioning
confidence: 99%